Genetic Interactions Reveal that Specific Defects of Chloroplast Translation are Associated with the Suppression of var2‐Mediated Leaf Variegation. Issue 10 (10th September 2013) - Liu, Xiayan; Zheng, Mengdi; Wang, Rui; Wang, Ruijuan; An, Lijun; Rodermel, Steve R.; Yu, Fei
Abstract Arabidopsis thaliana L. yellow variegated (var2) mutant is defective in a chloroplast FtsH family metalloprotease, AtFtsH2/VAR2, and displays an intriguing green and white leaf variegation. This unique var2‐mediated leaf variegation offers a simple yet powerful tool for dissecting the genetic regulation of chloroplast development. Here, we report the isolation and characterization of a new var2 suppressor gene, SUPPRESSOR OF VARIEGATION8 (SVR8), which encodes a putative chloroplast ribosomal large subunit protein, L24. Mutations in SVR8 suppress var2 leaf variegation at ambient temperature and partially suppress the cold‐induced chlorosis phenotype of var2. Loss of SVR8 causes unique chloroplast rRNA processing defects, particularly the 23S–4.5S dicistronic precursor. The recovery of the major abnormal processing site in svr8 23S–4.5S precursor indicate that it does not lie in the same position where SVR8/L24 binds on the ribosome. Surprisingly, we found that the loss of a chloroplast ribosomal small subunit protein, S21, results in aberrant chloroplast rRNA processing but not suppression of var2 variegation. These findings suggest that the disruption of specific aspects of chloroplast translation, rather than a general impairment in chloroplast translation, suppress var2 variegation and the existence of complex genetic interactions in chloroplast development.